PENGARUH KEPUASAN KERJA DAN BUDAYA ORGANISASI TERHADAP PERILAKU CITIZENSHIP KARYAWAN PT. LONTAR PAPYRUS PULP & PAPER INDUSTRY KABUPATEN TANJUNG JABUNG BARAT JAMBI - Johannes .; Paul Silitonga (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2013)
The aimed of this research is to determine the influence of job satisfaction and organizational culture on employee citizenship behavior of Lontar Papyrus Pulp & Paper Industry., Ltd West Tanjung Jabung Resident, Jambi. Researchâ€™s sample was chosen form several determined divisions that consists of 160 employees. The results shows that job satisfaction, organization culture and dummy variable (tenure) are simultaneously have positive and significant effect on employee citizenship behavior. But partially, organizational culture is the only ones that have positive and significant effect on employee citizenship behavior. Meanwhile, job satisfaction and dummy variable (tenure) do not have significant effect on employee citizenship behavior. Hence, it is recommended that develops culture to make more significant impact on firms performance. Keywords. . Lonthar Papyrus, Citezenship Behavior, kepuasan kerja, budaya kerja Â